2016
DOI: 10.1080/2162402x.2015.1093722
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine patterns in cancer patients: A review of the correlation between interleukin 6 and prognosis

Abstract: Objective: In tumor patients, IL-6 appears to be one component of a consistent cancer-associated cytokine network resulting in both a systemic immune stimulation and a microenvironment of cancer-induced immune suppression that ultimately protects the cancer cells. IL-6 has been associated with prognosis in cancer patients, but so far a systemical analysis has not been carried out. Methods: The present meta-analysis studies the relation between IL-6 serum levels and the prognosis of cancer patients in the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(167 citation statements)
references
References 155 publications
(168 reference statements)
6
156
3
2
Order By: Relevance
“…Interestingly, the soluble receptors of TNF-α (sTNFR1 and sTNFR2) inhibit the biologic activity of their ligand and act as antagonists; while the sIL-6R amplifies IL-6-mediated signaling [48]. Nevertheless, IL-6 is produced by many cell lineages, including fibroblasts, muscle cells, endothelial cells, keratinocytes, macrophages, T cells and mast cells [49, 50] . IL-6 can also be produced by adipocytes and adipose-derived stromal cells or stromal vascular fraction (SVF) [51], as well as by cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the soluble receptors of TNF-α (sTNFR1 and sTNFR2) inhibit the biologic activity of their ligand and act as antagonists; while the sIL-6R amplifies IL-6-mediated signaling [48]. Nevertheless, IL-6 is produced by many cell lineages, including fibroblasts, muscle cells, endothelial cells, keratinocytes, macrophages, T cells and mast cells [49, 50] . IL-6 can also be produced by adipocytes and adipose-derived stromal cells or stromal vascular fraction (SVF) [51], as well as by cancer cells [49].…”
Section: Discussionmentioning
confidence: 99%
“…En los cánceres de mama, riñón, próstata y mieloma múltiple se ha correlacionado con mal pronóstico y agresividad tumoral. Estudios recientes sitúan a la IL-6 como un regulador positivo del factor de crecimiento endotelial vascular (VEGF, vascular endothelial growth factor) 24,25 . Se ha encontrado que los valores de IL-6 circulante en las pacientes con cáncer de mama son 10 veces mayores que en las mujeres sanas, existiendo una correlación entre los valores más altos de IL-6 y los estadios más avanzados del cáncer de mama 24,26 .…”
Section: Introductionunclassified
“…This is indicative of influence of cancer on markers of immune system. On the other hand, inflammation and immune dysfunction has been associated in the pathology of cognitive dysfunction [1]. It has been reported that the oncologic treatment like chemotherapy leads to increased levels of cytokines [2].…”
Section: Risk Factors For Pocd In Cancer Patientsmentioning
confidence: 99%
“…The reported incidence of POCD varies due to lack of formal criteria for diagnosis of POCD. The various factors leading to POCD in cancer patients are demographic factors such as advanced age and comorbidities, genetic, immune factors and treatment related of which surgery and anaesthesia play a significant role [1][2][3][4][5].…”
mentioning
confidence: 99%